Alometric model to estimate the potential of carbure capture in Polylepis spp in Poccrac, Ancash 2016 - Ramírez Apolinario, Eleuterio (2018)
In the following study, allometric equations have been generated to estimate the aerial forest biomass of two species: Polylepis incana and Polylepis sericea, from an Andean natural forest located in the village of Poccrac, in the heights of Ticapampa, Ancash.The allometric equations for both species have been designed from 15 data, relating the biomass (M) as a dependent variable with the diameter of breast height as an independent variable (DAP). The DAP measurement of the selected Polylepis trees are within the range of 5 cm to 20 cm. In the regression analysis performed with the statistical program SPSS V 22.0, a correlation coefficient of r2 = 0.929 is found for the Polylepis incana species and a r2 = 0.94 for the Polylepis sericea species, which indicates a high relation between the biomass variables and DAP, showing good goodness of fit for the parameters that constitute the allometric equation of both species.The results obtained constitute an important methodological contribution for the estimates of carbon capture in areas destined for conservation and a tool to assess the CO2 capture function in Andean forests